Capitellum Fracture Fragment Excision: a Case Series - Garner, Matthew R. (HSS J, 2015)
BACKGROUND: Fractures of the capitellum are rare injuries, and few studies have reported the results of fragment excision. QUESTIONS/PURPOSES: The purpose of this study was to determine range of motion and short-term clinical outcomes for patients treated with capitellum excision. METHODS: A retrospective review was performed to identify all patients with an isolated capitellum fracture who underwent excision as definitive treatment at our institutions. Mechanism of injury, associated elbow injuries, type of capitellum fracture, complications, and postoperative outcomes including final elbow range of motion (ROM), elbow instability, and Disabilities of the Arm, Shoulder and Hand (DASH) score were recorded. RESULTS: Four patients met the inclusion and exclusion criteria of this study. All patients were female with an average age of 69 years (range 42–85). Based on the Bryan and Morrey classification system, three (75%) fractures were classified as type I and one (25%) fracture as type III. The average clinical follow-up was 11 months. Final examination demonstrated a mean elbow range of motion from 14° (range 0–30) of extension to 143° (range 130–160) of flexion. All patients had full forearm rotation, and there was no clinical evidence of elbow instability. The average DASH score was 18.3 (12.5–24.2) at final follow-up. CONCLUSION: Excision of the capitellum, much like excision of the radial head, results in acceptable short-term outcome scores and elbow range of motion in patients with fractures that are not amenable to open reduction and internal fixation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11420-015-9452-x) contains supplementary material, which is available to authorized users.